Composite nano defoaming agent, preparation method thereof, desulfurizing agent and application

By using composite nano-defoaming agents prepared by nano-silica and nano-alumina composite materials and surfactants, the problems of low defoaming efficiency, low stability and high toxicity of selective desulfurization amine solution in the prior art are solved, and efficient, stable and environmentally friendly defoaming effect is achieved, and the efficiency and performance of selective desulfurization are improved.

CN119909417APending Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311420512.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-30
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In the prior art, the defoaming agent of the selective desulfurizing amine solution has low defoaming efficiency, low stability and high toxicity, which affects the efficiency and stability of the desulfurization system.

Method used

Compound nano-defoaming agent is used, which consists of nano-silica and nano-alumina composite materials and surfactants. It is prepared by stirring, mixing, washing and drying. It has a high specific surface area and strong surfactivity, and can effectively adsorb and disperse foam, achieving efficient defoaming and long-term foam suppression.

Benefits of technology

The composite nano defoamer has a defoaming rate of 90% at 140°C and a pH of 2-12, and the defoaming time is less than 10 seconds. It can meet the needs of harsh industrial environments, and is environmentally friendly and low-toxic, reducing environmental pollution. Used in combination with amine liquid improves the efficiency and performance of selective desulfurization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004520948580000121
    Figure BDA0004520948580000121
  • Figure BDA0004520948580000122
    Figure BDA0004520948580000122
  • Figure BDA0004520948580000131
    Figure BDA0004520948580000131
Patent Text Reader

Abstract

The invention relates to the field of gas purification, and discloses a composite nano defoaming agent, a preparation method thereof, a desulfurizing agent and application. The defoaming agent comprises a nano composite material and a surfactant; the nano composite material comprises nano silicon dioxide and nano aluminum oxide; wherein the molar ratio of the nano silicon dioxide to the nano aluminum oxide is (1: 1)-(3: 1); the average particle size of the nano silicon dioxide is 5-50nm, and the specific surface area is 100-200m < 2 > / g; the average particle size of the nano aluminum oxide is 1-100nm, and the specific surface area is 50-300m < 2 > / g. The composite nano defoaming agent provided by the invention is high in defoaming efficiency, high in stability, capable of inhibiting foam for a long time, green and safe, simple in preparation method and capable of adapting to various severe industrial environments, and a desulfurizing agent obtained by matching with amine liquid has relatively high selective desulfurization efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of gas purification, and in particular to a composite nano defoamer and a preparation method thereof, a desulfurizer and application thereof. Background Art

[0002] Natural gas, refinery gas, biomass combustion gas and other gases usually contain H2S and CO2. H2S is a highly toxic gas that threatens personal safety and causes corrosion of equipment and pipelines. H2S and other sulfides must be removed before processing and transportation. Selective desulfurization technology has become an important research direction for deacidification technology. Selective desulfurization amine liquid has some special requirements, the most important of which are high H2S absorption selectivity and high regeneration energy consumption. In order to meet these requirements, some additives are often needed to adjust the chemical and physical properties of the amine liquid. However, these additives often affect the foaming characteristics of the amine liquid, causing the amine liquid to produce foam, thereby affecting the efficiency and stability of the selective desulfurization system.

[0003] With the increasing attention paid to the foaming phenomenon in production, adding defoamers has become the main application method in various industries. Compared with traditional defoaming and foam suppression methods, the use of defoamers has the advantages of fast defoaming speed, long foam suppression time, and no impact on the production process. Traditional defoamers include polyether type, silicone type, amide type, polyether mixed type, etc. By adding defoamers, they can be adsorbed on the foam surface to form a surface film layer, and finally break the foam. However, polyether defoamers are prone to decomposition and oxidation, which reduces the defoaming effect and produces toxicity; silicone defoamers are prone to thermal decomposition under high temperature and high pressure conditions, reducing the defoaming effect; amide defoamers are easily affected by the environment, such as changes in temperature and pH value, which reduces the defoaming effect; polyether mixed defoamers: have low surface tension, but are also prone to decomposition and degradation, affecting their defoaming effect. At the same time, these defoamers may also be toxic and pollute the environment. In addition, there is currently little research on defoamers for selective desulfurization amine liquid, and the use of single defoamers and compound defoamers lacks systematic and targeted guidance.

[0004] Therefore, there is an urgent need to develop a defoaming agent with high stability, high defoaming efficiency, low environmental pollution and excellent performance to solve the problems faced by the selective desulfurization amine liquid in defoaming. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of low defoaming efficiency, low stability and high toxicity of defoaming agents in the prior art, and to provide a composite nano defoaming agent and a preparation method thereof, a desulfurizing agent and application thereof. The composite nano defoaming agent has high defoaming efficiency, high stability, can suppress foam for a long time, is green and safe, has a simple preparation method, can adapt to various harsh industrial environments, and the desulfurizing agent obtained by combining with amine solution has higher selective desulfurization efficiency.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a composite nano defoamer, wherein the defoamer comprises a nano composite material and a surfactant; the nano composite material comprises nano silicon dioxide and nano aluminum oxide;

[0007] Wherein, the molar ratio of nano silicon dioxide to nano aluminum oxide is 1:1-3:1;

[0008] The average particle size of the nano-silicon dioxide is 5-50nm, and the specific surface area is 100-200m 2 / g;

[0009] The average particle size of the nano-alumina is 1-100 nm, and the specific surface area is 50-300 m 2 / g.

[0010] The second aspect of the present invention provides a method for preparing a composite nano defoamer, wherein the method comprises:

[0011] The nano composite material and the surfactant are stirred and mixed, and then washed and dried to obtain the composite nano defoaming agent.

[0012] The third aspect of the present invention provides a desulfurizing agent, wherein the desulfurizing agent comprises: an amine solution and the composite nano defoaming agent described in the first aspect or the composite nano defoaming agent prepared by the method described in the second aspect.

[0013] The fourth aspect of the present invention provides a use of the desulfurization agent described in the third aspect for selectively removing H2S from a CO2-containing gas mixture.

[0014] Through the above technical solution, the present invention has the following beneficial effects:

[0015] (1) The composite nano defoamer provided by the present invention uses nano silicon dioxide and nano aluminum oxide in combination. The nano silicon dioxide used has a small particle size, a large specific surface area, and a large number of surface atoms. There are abundant surface active sites on the surface of the nano silicon dioxide, which has chemical reactivity, strong adsorption capacity, and strong hydrophilicity. The surface free energy of nano aluminum oxide is relatively high, and its nanometer-scale particle size and high dispersibility can increase the specific surface area and active sites. The combination of nano silicon dioxide and nano aluminum oxide has an obvious synergistic effect, promotes the dispersion of raw materials, and enhances the defoaming efficiency, stability, and durability of the composite nano defoamer.

[0016] (2) The composite nano defoamer provided by the present invention adopts composite nano materials in combination with surfactants. The obtained composite nano defoamer has a large specific surface area and strong surface activity, and can be effectively adsorbed and dispersed on the foam surface, thereby reducing the surface tension, destroying the foam structure, and achieving a defoaming effect. At the same time, the surfactant can form a molecular film on the liquid surface, reduce the surface tension of the liquid, prevent the regeneration of foam and the extension of foam, and achieve efficient defoaming and long-term foam suppression.

[0017] (3) The composite nano defoamer provided by the present invention has a defoaming rate of more than 90% at 140°C and a pH of 2-12, and a defoaming time of less than 10 seconds, which can meet the needs of various harsh industrial environments; and the preparation method of the composite nano defoamer is simple, the raw materials are easily available, and the cost is low. Compared with traditional chemical defoamers, it is more environmentally friendly and less toxic, and can reduce pollution to the environment.

[0018] (4) The desulfurization agent provided by the present invention is prepared from a composite nano-defoaming agent and an amine liquid, and is used to selectively remove H2S from carbon dioxide. During the selective desulfurization process, the active substances in the amine liquid react chemically with the H2S molecules in the gas mixture to absorb and remove H2S. The composite nano-defoaming agent has a large specific surface area and activity, and can provide more active substances to adsorb and remove H2S, thereby promoting highly selective desulfurization of the amine liquid and improving the efficiency and performance of the selective desulfurization. DETAILED DESCRIPTION

[0019] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0020] The first aspect of the present invention provides a composite nano defoamer, wherein the defoamer comprises a nano composite material and a surfactant; the nano composite material comprises nano silicon dioxide and nano aluminum oxide;

[0021] Wherein, the molar ratio of nano silicon dioxide to nano aluminum oxide is 1:1-3:1;

[0022] The average particle size of the nano-silicon dioxide is 5-50nm, and the specific surface area is 100-200m 2 / g;

[0023] The average particle size of the nano-alumina is 1-100 nm, and the specific surface area is 50-300 m 2 / g.

[0024] In the present invention, the molar ratio of nano-silicon dioxide to nano-aluminum oxide is 1:1-3:1, and can be 1:1, 1.25:1, 1.5:1, 1.75:1, 2:1, 2.25:1, 2.5:1, 2.75:1, 3:1 and any value in the range formed by any two of these point values. Meeting this range is conducive to achieving the best defoaming effect of the composite nano defoamer. The molar ratio of the nano-silicon dioxide to the nano-alumina is greater than 3:1, that is, the nano-silicon dioxide is excessive. The large amount of nano-silicon dioxide will cover the active sites of the nano-alumina, weaken the surface activity, reduce its adsorption and reaction capabilities, affect the synergistic effect between the defoamer and the corrosive gas, and reduce the defoaming effect and selectivity; the molar ratio of the nano-silicon dioxide to the nano-alumina is less than 1:1, that is, the nano-alumina is excessive. The excessive presence of nano-alumina will lead to a decrease in the specific surface area of ​​the defoamer, reduce the contact area between the defoamer and the gas, thereby affecting its adsorption and reaction efficiency, and less nano-silicon dioxide cannot provide enough active sites to remove corrosive gases, resulting in a decrease in the selectivity of the defoamer.

[0025] In the present invention, excessive nano-silicon dioxide or nano-alumina will reduce the anti-corrosion performance of the defoaming agent on the device, causing unnecessary deposition or blockage, reducing the fluidity of the device, and thus affecting the anti-corrosion performance. In the present invention, the average particle size of the nano-silicon dioxide is 5-50nm, and the specific surface area is 100-200m 2 The nano silicon dioxide has a small average particle size, a high specific surface area and a high reactivity, and the active surface hydroxyl groups give it a strong adsorption capacity and hydrophilicity, which is conducive to adsorption on the gas-liquid interface, thereby destroying the foam structure and achieving a defoaming effect.

[0026] In the present invention, the average particle size of the nano-alumina is 1-100nm, and the specific surface area is 50-300m 2 / g. The nano-alumina has a nano-scale particle size and high dispersibility, which is beneficial to increase the surface area and active sites of the composite nano-defoamer, improve the defoaming efficiency and defoaming stability, and has a significant synergistic effect when combined with nano-silicon dioxide, promotes the dispersion of raw materials, and further enhances the defoaming efficiency, stability and durability of the composite nano-defoamer.

[0027] In some embodiments of the present invention, preferably, based on the total amount of the composite nano defoamer, the content of the surfactant in the composite nano defoamer is 0.5-2 wt %.

[0028] In some embodiments of the present invention, preferably, the surfactant is selected from at least one of octanol polyoxyethylene ether, octylphenol polyoxyethylene ether and sodium dodecylbenzene sulfonate, preferably octanol polyoxyethylene ether.

[0029] In the present invention, the surfactant has good hydrophilicity and can form a molecular film on the liquid surface, reduce the surface tension of the liquid, prevent the regeneration and extension of foam, and achieve efficient defoaming and long-term foam suppression; in addition, the surfactant can promote the dispersion and stabilization of nano-silicon dioxide and nano-aluminum oxide.

[0030] In some embodiments of the present invention, preferably, the defoaming rate of the defoaming agent at 140° C. and pH 2-12 is greater than 90%, and the defoaming time is less than 10 s.

[0031] The second aspect of the present invention provides a method for preparing a composite nano defoamer, wherein the method comprises:

[0032] The nano composite material and the surfactant are stirred and mixed, and then washed and dried to obtain the composite nano defoaming agent.

[0033] In some embodiments of the present invention, preferably, the stirring speed is 500-800 rpm and the stirring time is 8-12 hours. In the present invention, the stirring conditions are conducive to fully dispersing the surfactant.

[0034] In some embodiments of the present invention, preferably, the washing liquid is selected from any one of deionized water, ethanol and acetone, preferably ethanol.

[0035] In the present invention, there is no particular requirement for the washing method. For example, the product obtained after stirring and mixing can be mixed with a washing liquid, stirred for 2-4 hours, left to stand for 2-3 hours and then separated, and the above washing process is repeated 2-5 times. Preferably, in order to achieve a better washing effect, the washing liquid and the product obtained after stirring and mixing can be stirred quickly during the mixing process.

[0036] In some embodiments of the present invention, preferably, the method for preparing the nanocomposite material comprises:

[0037] (1) dissolving a nano-silicon dioxide precursor and a nano-aluminum oxide precursor in a solvent, and stirring the mixture under constant temperature and humidity conditions to form a sol;

[0038] (2) subjecting the sol to ultrasonic dispersion and static mixing to form a uniform mixture;

[0039] (3) adding a surfactant to the mixture, stirring to gelate, and forming a solid gel;

[0040] (4) Drying the gel to obtain the nanocomposite material.

[0041] In some embodiments of the present invention, preferably, in step (1), the solvent is selected from any one of acetone, ethanol and deionized water. In the present invention, the solvent is conducive to the full dispersion of the nanomaterial.

[0042] In some embodiments of the present invention, preferably, based on the total amount of the nano-silicon dioxide precursor and the nano-aluminum oxide, the amount of the solvent is 60-70 wt %.

[0043] In some embodiments of the present invention, preferably, the constant temperature and humidity conditions include: temperature of 20-30° C., relative humidity of 40-60%; stirring time of 8-12 h, stirring speed of 300-500 rpm.

[0044] In some embodiments of the present invention, preferably, in step (2), the ultrasonic time is 30-60 min, the frequency is 20-50 kHz, and the power is 200-500 W; and the standing time is 2-4 h.

[0045] In the present invention, in step (2), the sol is subjected to ultrasonic treatment, and the ultrasonic treatment is carried out in a tip oscillator, the frequency of the ultrasound is 20-50kHz, and the power is 200-500W, which is more conducive to promoting the dispersion and mixing of the sol to form a uniform mixture; in addition, after the ultrasonic treatment for 30-60min, it is allowed to stand for 2-4h to allow the system to be fully mixed.

[0046] In some embodiments of the present invention, preferably, in step (3), the catalyst is selected from ammonia water and / or ammonium nitrate.

[0047] In some embodiments of the present invention, preferably, based on the total amount of nano-silicon dioxide precursor and nano-aluminum oxide, the amount of the catalyst is 0.2-5 wt %.

[0048] In some embodiments of the present invention, preferably, in step (3), the gelation conditions include: temperature of 80-120°C, heating rate of 0.5-2°C / min, time of 2-6h, and pH of 7-9.

[0049] In some embodiments of the present invention, preferably, in step (3), the stirring speed is 300-500 rpm. In the present invention, in step (3), the mixture is heated to 80-120°C, a surfactant is added, and the sol is gelled to form a solid gel, wherein the pH of the gelation is 7-9, which is conducive to making the gel have excellent stability.

[0050] In some embodiments of the present invention, preferably, in step (4), the drying temperature is 100-150° C. and the drying time is 8-12 hours. In the present invention, the solid gel is dried to remove the solvent and water to form the nanocomposite material.

[0051] The third aspect of the present invention provides a desulfurizing agent, wherein the desulfurizing agent comprises: an amine solution and the composite nano defoaming agent described in the first aspect or the composite nano defoaming agent prepared by the method described in the second aspect.

[0052] In the present invention, the nano defoamer is a composite of nano silicon dioxide and nano aluminum oxide, and has a smaller particle size and a higher specific surface area. After the nano defoamer is added to the amine solution, the nano particles can diffuse in the amine solution and adsorb on the bubble surface, thereby preventing the formation and aggregation of bubbles.

[0053] In some embodiments of the present invention, preferably, the volume ratio of the composite nano defoamer to the amine liquid is 1-20:10000. Within this range, it is beneficial for the composite nano defoamer to obtain a good defoaming effect. In the present invention, an excess of the composite nano defoamer will cause the defoamer to be over-dispersed in the liquid phase, affecting its adsorption and destructive capabilities at the gas-liquid interface, and the excess defoamer reacts with other components of the amine liquid to form unstable substances, affecting the defoaming effect; if the composite nano defoamer is too little, the defoaming effect is not obvious, and the actual industrial needs are not met.

[0054] In some embodiments of the present invention, preferably, the amine solution is an aqueous solution of one or more amines.

[0055] In some embodiments of the present invention, preferably, the concentration of the amine solution is 30-45 wt %.

[0056] In some embodiments of the present invention, preferably, the amine is selected from N-methyldiethanolamine and / or diethanolamine.

[0057] In some embodiments of the present invention, preferably, the composite nano defoamer is used at a temperature of 25-140° C. and a pressure of 0.5-9 MPa; the composite nano defoamer within this range has a good defoaming effect.

[0058] The fourth aspect of the present invention provides a use of the desulfurization agent described in the third aspect for selectively removing H2S from a CO2-containing gas mixture.

[0059] In some embodiments of the present invention, preferably, the content of CO2 in the gas mixture is 0.1-25v%, and the content of H2S is 0.1-5v%. In the present invention, the composite nano defoamer is used at a temperature of 25-140°C and a pressure of 0.5-9MPa. The gas concentrations of CO2 and H2S in the gas mixture are within the above ranges, which can effectively eliminate bubbles in the desulfurizer and achieve a good defoaming effect. When the gas concentrations of CO2 and H2S in the gas mixture exceed the above ranges, the CO2 and H2S in the gas mixture increase significantly, and the amount of the defoamer cannot meet the amount of foam, resulting in a reduced defoaming effect.

[0060] The present invention will be described in detail below through examples.

[0061] Example 1

[0062] (1) 8.8 g of nano-silicon dioxide (average particle size 30 nm, specific surface area 150 m 2 / g) and 10g nano-alumina (average particle size 80nm, specific surface area 200m 2 / g) was dissolved in 15.5mL of ethanol and stirred at 400rpm for 10h at 25°C and 50% relative humidity to form a sol;

[0063] (2) The sol was ultrasonically dispersed at a frequency of 40 kHz and a power of 350 W for 45 min, and then allowed to stand and mix for 3 h to form a uniform mixture:

[0064] (3) adding 0.2 g of aqueous ammonia to the mixture, stirring at a speed of 400 rpm for gelation to form a solid gel, wherein the gelation conditions include: temperature of 100° C., heating rate of 2° C. / min, time of 4 h, and pH of 8;

[0065] (4) drying the solid gel at 120° C. for 9 h to obtain a composite nanomaterial, then adding 0.2 g of octanol polyoxyethylene ether, and stirring at a speed of 600 rpm for 9 h to obtain the composite nano defoamer, which is recorded as defoamer 1;

[0066] (5) 5 mL of defoaming agent 1 was added into 10000 mL of N-methyldiethanolamine solution (40 wt%), and the mixture was stirred to obtain the desulfurizing agent.

[0067] Example 2

[0068] (1) 9 g of nano-silicon dioxide (average particle size 50 nm, specific surface area 200 m 2 / g) and 7.6g of nano-alumina (average particle size 80nm, specific surface area 200m 2 / g) was dissolved in 13.8mL of ethanol and stirred at 400rpm for 10h at 25°C and 50% relative humidity to form a sol;

[0069] (2) The sol was ultrasonically dispersed at a frequency of 40 kHz and a power of 350 W for 45 min, and then allowed to stand and mix for 3 h to form a uniform mixture:

[0070] (3) adding 0.2 g of aqueous ammonia to the mixture, stirring at a speed of 400 rpm for gelation to form a solid gel, wherein the gelation conditions include: temperature of 120° C., heating rate of 2° C. / min, time of 3.5 h, and pH of 8;

[0071] (4) drying the solid gel at 120° C. for 9 h to obtain a composite nanomaterial, then adding 0.2 g of octanol polyoxyethylene ether and stirring at a speed of 600 rpm for 9 h to obtain the composite nano defoamer, which is recorded as defoamer 2;

[0072] (5) 5 mL of defoamer 2 was added into 10000 mL of N-methyldiethanolamine solution (40 wt%), and the mixture was stirred to obtain the desulfurizing agent.

[0073] Example 3

[0074] (1) 11 g of nano-silicon dioxide (average particle size 20 nm, specific surface area 100 m 2 / g) and 7.7g nano-alumina (average particle size 50nm, specific surface area 300m 2 / g) was dissolved in 15.4mL of ethanol and stirred at 400rpm for 10h at 25°C and 50% relative humidity to form a sol;

[0075] (2) The sol was ultrasonically dispersed at a frequency of 40 kHz and a power of 350 W for 45 min, and then allowed to stand and mix for 3 h to form a uniform mixture:

[0076] (3) adding 0.2% ammonium nitrate to the mixture, stirring at a speed of 450 rpm for gelation to form a solid gel, wherein the gelation conditions include: temperature of 110° C., heating rate of 2° C. / min, time of 4 h, and pH of 8;

[0077] (4) drying the solid gel at 120° C. for 9 h to obtain a composite nanomaterial, then adding 0.2 g of octanol polyoxyethylene ether and stirring at a speed of 600 rpm for 9 h to obtain the composite nano defoamer, which is recorded as defoamer 3;

[0078] (5) 5 mL of defoaming agent 3 was added into 10000 mL of N-methyldiethanolamine solution (40 wt%), and the mixture was stirred to obtain the desulfurizing agent.

[0079] Example 4

[0080] The method of Example 1 is followed, except that

[0081] In step (1), 7 g of nano-silicon dioxide (average particle size 20 nm, specific surface area 150 m 2 / g) and 11.8g nano-alumina (average particle size 80nm, specific surface area 200m 2 / g) was dissolved in 15.5mL of ethanol to obtain the desulfurizing agent.

[0082] Example 5

[0083] According to the method of Example 1, the difference is that

[0084] In step (1), 12 g of nano-silicon dioxide (average particle size 30 nm, specific surface area 150 m 2 / g) and 6.8g nano-alumina (average particle size 80nm, specific surface area 200m 2 / g) was dissolved in 15.5mL ethanol;

[0085] In step (4), 0.38 g of octylphenol polyoxyethylene ether is used instead of octanol polyoxyethylene ether to obtain the desulfurizing agent.

[0086] Example 6

[0087] According to the method of Example 1, the difference is that

[0088] In step (1), the average particle size of nano-silicon dioxide is 20 nm and the specific surface area is 100 m 2 / g; the average particle size of nano-alumina is 40nm and the specific surface area is 150m 2 / g;

[0089] In step (4), 0.1 g of sodium dodecylbenzene sulfonate is used instead of octanol polyoxyethylene ether to obtain the desulfurizing agent.

[0090] Comparative Example 1

[0091] According to the method of Example 1, the difference is that

[0092] In step (1), 13.9 g of nano-silicon dioxide (average particle size 50 nm, specific surface area 300 m 2 / g), 4.8g nano-alumina (average particle size 20nm, specific surface area 100m 2 / g), to obtain the desulfurizing agent.

[0093] Comparative Example 2

[0094] According to the method of Example 1, the difference is that

[0095] In step (1), the desulfurizing agent is obtained without adding nano-alumina.

[0096] Comparative Example 3

[0097] According to the method of Example 1, the difference is that

[0098] In step (1), the composite nano defoamer is replaced by a commercially available conventional silicon defoamer;

[0099] In step (5), 50 mL of a commercially available traditional silicon defoamer is added to obtain the desulfurizing agent.

[0100] Comparative Example 4

[0101] The method of Example 1 was followed, except that no defoaming agent was added.

[0102] Desulfurization performance test:

[0103] The defoaming effect and desulfurization performance test results of the desulfurizers in Examples 1-6 and Comparative Examples 1-4 are shown in Table 1, and the defoaming rate and defoaming time test results of the desulfurizers in Examples 1-6 and Comparative Examples 1-4 under strong acid, strong alkali and high temperature (140°C) conditions are shown in Table 2, wherein the test pressure of the desulfurizers in Examples 1-6 and Comparative Examples 1-4 is 1 MPa.

[0104] Table 1 Defoaming effect and desulfurization performance test results

[0105]

[0106] Table 2 Defoaming rate and defoaming time test results

[0107]

[0108]

[0109] It can be seen from the results in Table 1 and Table 2 that the composite nano defoamer provided by the present invention has good defoaming effect and long-term foam suppression ability in the process of selective desulfurization, improves the absorption efficiency of amine solution and the selective desulfurization effect, and has good defoaming performance in an acid-base environment with a high temperature (140°C) and a pH of 2-12. It can be seen from Examples 1-6 in Table 1 that the molar ratio, average particle size and specific surface area of ​​nano-silicon dioxide and nano-alumina are simultaneously controlled within the range defined by the present invention, and the prepared composite nano defoamer can achieve efficient defoaming and long-term foam suppression, promote selective desulfurization of amine solution, and improve the efficiency and performance of selective desulfurization. Under high temperature (140°C) and acid-base conditions of pH 2-12, the defoaming rate of the composite nano defoamer is maintained at more than 90%, and the defoaming time is greater than 2h and less than 10s; Comparative Examples 1 and 2 do not use the molar ratio of nano-silicon dioxide and nano-alumina defined by the present invention, and the defoaming effect of the prepared defoamer is poor. Comparative Example 3 uses a commercially available traditional silicon defoamer, and the foam suppression effect is not obvious, and the foam suppression cannot be long-term, and the effect of selective desulfurization is not significantly improved; Comparative Example 4 does not add a defoamer, the defoaming effect is poor, the foam suppression cannot be long-term, and the selective desulfurization effect is poor.

[0110] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composite nano defoamer, characterized in that: The defoaming agent comprises a nanocomposite material and a surfactant; the nanocomposite material comprises nano silicon dioxide and nano aluminum oxide; Wherein, the molar ratio of nano silicon dioxide to nano aluminum oxide is 1:1-3:1; The average particle size of the nano-silicon dioxide is 5-50nm, and the specific surface area is 100-200m 2 / g; The average particle size of the nano-alumina is 1-100 nm, and the specific surface area is 50-300 m 2 / g.

2. The defoaming agent according to claim 1, wherein Based on the total amount of the composite nano defoamer, the content of the surfactant in the composite nano defoamer is 0.5-2wt%; Preferably, the surfactant is selected from at least one of octanol polyoxyethylene ether, octylphenol polyoxyethylene ether and sodium dodecylbenzene sulfonate, preferably octanol polyoxyethylene ether.

3. The defoaming agent according to claim 1 or 2, wherein The defoaming rate of the defoaming agent is greater than 90% under the conditions of 140° C. and pH 2-12, and the defoaming time is less than 10 seconds.

4. A method for preparing a composite nano defoamer, characterized in that: The method includes: The nanocomposite material and the surfactant are stirred and mixed, and then washed and dried to obtain the composite nano defoamer; Preferably, the stirring speed is 500-800 rpm, and the stirring time is 8-12 h; Preferably, the washing liquid is selected from any one of deionized water, ethanol and acetone, preferably ethanol.

5. The method according to claim 4, wherein: The preparation method of the nanocomposite material comprises: (1) dissolving a nano-silicon dioxide precursor and a nano-aluminum oxide precursor in a solvent, and stirring the mixture under constant temperature and humidity conditions to form a sol; (2) subjecting the sol to ultrasonic dispersion and static mixing to form a uniform mixture; (3) adding a catalyst to the mixture, stirring to carry out gelation, and forming a solid gel; (4) Drying the gel to obtain the nanocomposite material.

6. The method according to claim 5, wherein: In step (1), the solvent is selected from any one of acetone, ethanol and deionized water; Preferably, the amount of the solvent is 60-70wt% based on the total amount of the nano-silicon dioxide precursor and the nano-aluminum oxide; Preferably, the constant temperature and humidity conditions include: temperature of 20-30°C, relative humidity of 40-60%; stirring time of 8-12h, stirring speed of 300-500rpm; Preferably, in step (2), the ultrasonic time is 30-60 min, the frequency is 20-50 kHz, and the power is 200-500 W; the standing time is 2-4 h; Preferably, in step (3), the catalyst is selected from ammonia water and / or ammonium nitrate; Preferably, the amount of the catalyst is 0.2-5wt% based on the total amount of the nano-silicon dioxide precursor and the nano-aluminum oxide; Preferably, the gelation conditions include: temperature of 80-120°C, heating rate of 0.5-2°C / min, time of 2-6h, pH of 7-9; stirring speed of 300-500rpm; Preferably, in step (4), the drying temperature is 100-150° C., and the drying time is 8-12 h.

7. A desulfurizing agent, characterized in that: The desulfurizing agent comprises: an amine solution and the composite nano defoaming agent described in any one of claims 1 to 3 or the composite nano defoaming agent prepared by the method described in any one of claims 4 to 6.

8. The desulfurizing agent according to claim 7, wherein The volume ratio of the composite nano defoamer to the amine solution is 1-20:10000.

9. The desulfurizing agent according to claim 7 or 8, wherein The amine solution is an aqueous solution of one or more amines; Preferably, the concentration of the amine solution is 30-45wt%; Preferably, the amine is selected from N-methyldiethanolamine and / or diethanolamine; Preferably, the composite nano defoamer is used at a temperature of 25-140° C. and a pressure of 0.5-9 MPa.

10. Use of the desulfurizing agent according to any one of claims 7 to 9 in selectively removing H2S from a CO2-containing gas mixture; Preferably, the CO2 content in the gas mixture is 0.1-25v%, and the H2S content is 0.1-5v%.